Pills, PrEP, and Pals: Adherence, Stigma, Resilience, Faith and the Need to Connect Among Minority Women With HIV/AIDS in a US HIV Epicenter - Duthely, Lunthita M.; Sanchez-Covarrubias, Alex P.; Brown, Megan R.; Thomas, Tanya E.; Montgomerie, Emily K.; Dale, Sannisha; Safren, Steven A.; Potter, JoNell E. (Frontiers in Public Health, 2021)
Background: Ending HIV/AIDS in the United States requires tailored interventions. This study is part of a larger investigation to design mCARES, a mobile technology-based, adherence intervention for ethnic minority women with HIV (MWH). Objective: To understand barriers and facilitators of care adherence (treatment and appointment) for ethnic MWH; examine the relationship between these factors across ethnic groups; and, explore the role of mobile technologies in care adherence. Methods: Cross-sectional, mixed-methods data were collected from African-American, Hispanic-American and Haitian- American participants. A focus group (n=8) assessed barriers and facilitators to care adherence. We surveyed women (n=48) on depression (PHQ-9), HIV-related stigma (HSS) and resiliency (CD-RISC25), and examined the relationships between these factors and adherence to treatment and to care and across groups. Findings: Qualitatively, barriers to treatment and appointment adherence were caregiver-related stressors (25%) and structural issues (25%); routinization (30%) and religion/spirituality (30%) promoted adherence to treatment and care. Caregiver role was both a hindrance (25%) and promoter (20%) of adherence to treatment and appointments. Quantitatively, HIV-related stigma differed by ethnic group; Haitian-Americans endorsed the highest levels while African-Americans endorsed the lowest. Depression correlated to stigma (R=.534; p<0.001) and resiliency (R=-0.486; p<0.001). Overall, higher depression and stigma were related to viral non-suppression (p<0.05); higher resiliency was related to viral suppression. Among Hispanic-Americans, viral non-suppression was related to depression (p<0.05), and among African-Americans, viral suppression was related to increased resiliency (p<0.04). Conclusion: Multiple interrelated barriers to adherence were identified. These findings on ethnic group-specific differences underscore the importance of implementing culturally-competent interventions.